The Economics of Animal Health and Production - Rushton, Jonathan (CABI, 2014)
During the last 200 years, there has been massive socio-economic change through industrial and agricultural revolutions. This change has been associated with rapid increases in human and domestic livestock populations, and a movement of people from rural to urban areas. More than half the people in the world now live in urban environments where they have better access to work, but limited or no access to land and livestock to produce food. This implies that a majority of people are dependent on others for raw, semi-processed and processed food products. The efficient functioning of the livestock sector, encompassing all facets of input supply, production, processing and marketing, has become a critical issue for guaranteeing: ● that sufficient livestock products are available at affordable prices – food security; and ● that the livestock products are safe to eat – food safety. Within the livestock sector, the livestock producers and business people involved in input supply and output processing and marketing need to be able to plan, make a profit and have a sustainable livelihood. The State also plays a critical role in facilitating how the livestock sector functions and develops in order to satisfy society’s needs. Therefore, both the private and public sectors require economic theory and tools to understand the drivers of change for the livestock sector, and how to assess the impact of future actions and investments.